2021
DOI: 10.1186/s13550-021-00752-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased [18F]FMISO accumulation under hypoxia by multidrug-resistant protein 1 inhibitors

Abstract: Background [18F]Fluoromisonidazole ([18F]FMISO) is a PET imaging probe widely used for the detection of hypoxia. We previously reported that [18F]FMISO is metabolized to the glutathione conjugate of the reduced form in hypoxic cells. In addition, we found that the [18F]FMISO uptake level varied depending on the cellular glutathione conjugation and excretion ability such as enzyme activity of glutathione-S-transferase and expression levels of multidrug resistance-associated protein 1 (MRP1, an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…PCTAIRE-3 is mainly expressed in differentiated neurones and has been linked to Alzheimer's disease pathology, both relating to amyloid precursor protein-dependent Alzheimer's pathology via phosphorylation [83] and by regulation of tau phosphorylation [84]. Multidrug resistance-associated protein 7 was identified in the hypoxia EV citrullinome; although deimination needs to be studied in this context, multidrug resistance is linked to hypoxia [85]. G-protein-coupled receptor 19 was identified in the EV citrullinome in hypoxia, and although effects of its deimination have not been reported, it has been linked to neonatal HI-induced brain damage [86].…”
Section: Ev Citrullinome Signatures In Normoxia-and Hypoxia-treated N...mentioning
confidence: 99%
“…PCTAIRE-3 is mainly expressed in differentiated neurones and has been linked to Alzheimer's disease pathology, both relating to amyloid precursor protein-dependent Alzheimer's pathology via phosphorylation [83] and by regulation of tau phosphorylation [84]. Multidrug resistance-associated protein 7 was identified in the hypoxia EV citrullinome; although deimination needs to be studied in this context, multidrug resistance is linked to hypoxia [85]. G-protein-coupled receptor 19 was identified in the EV citrullinome in hypoxia, and although effects of its deimination have not been reported, it has been linked to neonatal HI-induced brain damage [86].…”
Section: Ev Citrullinome Signatures In Normoxia-and Hypoxia-treated N...mentioning
confidence: 99%
“…When 18 F-FMISO enters living cells, the nitro group of FMISO is reduced. In nonhypoxic cells, reduced FMISO molecules can be oxidized to diffuse into the free extracellular circulation and ultimately excreted [148][149][150]. However, in hypoxic tumor cells, this oxidation does not occur and the FMISO molecules accumulate.…”
Section: -Nitroimidazolementioning
confidence: 99%
“…Another widely studied class of agents is the Cu complex with diacetyl-bis(N4-methylthiosemicarbazone) (ATSM) ligand, among which ATSM is the prototype (Figure 5). Fujibayashi [60][61][62][63][64] Cu isotope to label some compounds such as ATSM and used the synthesized 62 Cu-ATSM to study cardiac perfusion in a rat model. Their findings suggested that 62 Cu-ATSM could accumulate during hypoxia.…”
Section: -64 Cumentioning
confidence: 99%
“…Fujibayashi [60][61][62][63][64] Cu isotope to label some compounds such as ATSM and used the synthesized 62 Cu-ATSM to study cardiac perfusion in a rat model. Their findings suggested that 62 Cu-ATSM could accumulate during hypoxia. Similarly, their studies on 64 Cu-ATSM, 18 F-FMISO, and 64 Cu-PTSM in EMT-6 tumor cells showed that 64 Cu-ATSM and 18 F-FMISO could differentially accumulate in tumors.…”
Section: -64 Cumentioning
confidence: 99%
See 1 more Smart Citation